2018
DOI: 10.1007/s00703-018-0653-y
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic fine aerosols dominate over the Pune region, Southwest India

Abstract: The major water-soluble ions, organic carbon (OC), elemental carbon (EC) and mass concentration of fine-(PM 2.5 ) and coarse-mode (PM 10-2.5 ) aerosols were measured at Pune during January-December 2016. The mass closure approach was used by comparing the sum of the masses of the individual chemical species to the gravimetric PM obtained by weighting the filter samples. The 1 year mean total mass concentration of fine and coarse mode was 40 µgm −3 (64%) and 23 µg m −3 (36%), respectively. The PM 2.5 /PM 10 rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…Na + , Ca 2+ , Mg 2+ and Cl − were found to have the highest concentrations during summer. Being land‐locked site and having low concentrations of Na + and Cl − in monsoon, it appears that the study site had little contributions from sea salt unlike those reported by George et al (2008) from Trivandrum; Gawhane et al (2019) from Pune; Chatterjee et al (2010) from Darjeeling experiencing air masses originating from the Arabian Sea and Bay of Bengal during the monsoon. As reported in the previous literature, carbonate minerals of Ca 2+ and Mg 2+ are known to neutralize the particles or rainwater acidity of anthropogenic pollutants (HNO 3 and H 2 SO 4 ) forming CaSO 4 and Ca(NO 3 ) 2 (P. Kumar et al, 2014).…”
Section: Resultsmentioning
confidence: 51%
“…Na + , Ca 2+ , Mg 2+ and Cl − were found to have the highest concentrations during summer. Being land‐locked site and having low concentrations of Na + and Cl − in monsoon, it appears that the study site had little contributions from sea salt unlike those reported by George et al (2008) from Trivandrum; Gawhane et al (2019) from Pune; Chatterjee et al (2010) from Darjeeling experiencing air masses originating from the Arabian Sea and Bay of Bengal during the monsoon. As reported in the previous literature, carbonate minerals of Ca 2+ and Mg 2+ are known to neutralize the particles or rainwater acidity of anthropogenic pollutants (HNO 3 and H 2 SO 4 ) forming CaSO 4 and Ca(NO 3 ) 2 (P. Kumar et al, 2014).…”
Section: Resultsmentioning
confidence: 51%
“…Here, we used daily averaged air quality data obtained from in‐situ observations in 119 stations under the Central Pollution Control Board (CPCB) across India for PM2.5. OC, BC, and SO 4 measurement data are directly taken from different literature (Chatterjee et al., 2012; Das et al., 2015; Gawhane et al., 2019; Guttikunda et al., 2013; Joseph et al., 2012; Murari et al., 2015; Pant et al., 2015; Pipalatkar et al., 2014; Ram et al., 2012; Rastogi et al., 2014; Samiksha et al., 2017). These data are mainly used to compare the model‐simulated surface concentrations of PM2.5, OC, BC, and SO 4 over the Indian land mass.…”
Section: Observations Used For Evaluationmentioning
confidence: 99%
“…They emerge from both natural and anthropogenic activities like farming, engineering, coal burning, etc. [14][15][16][17]. Aerosols are diverse in nature, driven by troposphere rollers, whereas, eliminated either by dry deposition through clouds and precipitation progressions [18][19][20].…”
Section: Introductionmentioning
confidence: 99%